Kesantunan Berbahasa pada Penutur Bahasa Kerinci di Desa Baru Sungai Tutung Kecamatan Air Hangat Timur : Language Politeness of Kerinci Language Speakers in Desa Baru Sungai Tutung Air Hangat Timur Subdistrict - Sari, Welsa Laudia; Purba, Andiopenta; Yusra, Hilman (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to determine the forms of language politeness in Kerinci language speakers in Sungai Tutung Baru Village, Air Hangat Timur Subdistrict. This research uses a qualitative approach with descriptive research. The research data is in the form of speech from the Kerinci community in the New Village of Sungai Tutung, East Warm Water Subdistrict, Kerinci Regency. In the process of collecting data, researchers used several data collection techniques, namely using observation techniques, recording techniques used by researchers to record speaking activities, free techniques where researchers are not directly involved in speaking, and recording techniques to record data that are considered important and meet the criteria of language politeness principles in the communication process. This research uses Leech's politeness principle theory which includes six maxims: the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, the maxim of agreement and the maxim of sympathy. In his findings, the researcher found a form of politeness consisting of six maxims, namely the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, the maxim of agreement and the maxim of sympathy. The data generated in the speech of the Kerinci community in Sungai Tutung New Village in performing speech acts are 22 utterances of obeying principles which are divided into 4 utterances of the maxim of wisdom, 4 utterances of the maxim of generosity, 4 utterances of the maxim of praise, 2 maxims of humility, 2 maxims of agreement and 4 maxims of sympathy. Furthermore, it is found that the principle of violating manners is 3 utterances. 1 utterance violates the maxim of wisdom, 1 utterance violates the maxim of humility and 1 utterance violates the maxim of agreement.